Hubungan Tipe Keluarga dengan Status Gizi Balita - Jaya, Wiwiek Hidayati; Arul, Muhammad Syahrul Alam; Anto, Ambo (PT.Mantaya Idea Batara, 2022)
The nutritional status of toddlers is an important thing that every parent must pay attention to, because at the age of toddlers it is based on the fact that the malnutrition that occurs in this golden age is irreversible. The purpose of this study was to determine the relationship between family type and nutritional status of toddlers in Batang Kaluku Village, Gowa Regency. The research design used was Non-Experimental with a correlational research design through a Cross-Sectional approach, where family type as an independent variable and the nutritional status of toddlers as a dependent variable. The research has been carried out in Batang Kaluku Village RT 01 / RW 01. With cluster sampling technique. Data were obtained using questionnaire sheets. Data processing using Chi-Square statistical test with Yates Correction. Based on the relationship analysis of 48 respondents obtained nuclear families with good nutritional status of toddlers as many as 16 (33.3%) respondents, and less as many as 8 (16.7%) respondents. Meanwhile, large families with good toddler nutritional status were 8 (16.7%) respondents, and less than 16 (33.3%) respondents. The results of statistical tests using the Chi-Square test with Yates Correctioan obtained a calculated X2 value (4.083) > from X2 table (3.84), meaning Ho was rejected and Ha was accepted. The conclusion is that there is a relationship between family type and the nutritional status of toddlers in Batang Kaluku Village, Gowa Regency.